Bifunctional Fluorescent/Raman Nanoprobe for the Early Detection of Amyloid - Xia, Yang; Padmanabhan, Parasuraman; Sarangapani, Sreelatha; Gulyás, Balázs; Vadakke Matham, Murukeshan (Scientific reports, 2019)
One of the pathological hallmarks of Alzheimer’s disease (AD) is the abnormal aggregation of amyloid beta (Aβ) peptides. Therefore the detection of Aβ peptides and imaging of amyloid plaques are considered as promising diagnostic methods for AD. Here we report a bifunctional nanoprobe prepared by conjugating gold nanoparticles (AuNPs) with Rose Bengal (RB) dye. RB is chosen due to its unique Raman fingerprints and affinity with Aβ peptides. After the conjugation, Raman signals of RB were significantly enhanced due to the surface-enhanced Raman scattering (SERS) effect. Upon binding with Aβ42 peptides, a spectrum change was detected, and the magnitude of the spectrum changes can be correlated with the concentration of target peptides. The peptide/probe interaction also induced a remarkable enhancement in the probes’ fluorescence emission. This fluorescence enhancement was further utilized to image amyloid plaques in the brain slices from transgenic mice. In this study, the RB-AuNPs were used for both SERS-based detection of Aβ42 peptides and fluorescence-based imaging of amyloid plaques. Compared to monofunctional probes, the multifunctional probe is capable to provide more comprehensive pathophysiological information, and therefore, the implementation of such multifunctional amyloid probes is expected to help the investigation of amyloid aggregation and the early diagnosis of AD.